2018
DOI: 10.1142/s1758825118500151
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Analysis-Based Optimal Selection of Cohesive Zone Model for Metallic Materials

Abstract: Five different cohesive zone models (CZMs), including bilinear, polynomial, trapezoidal, exponential, and PPR (Park–Paulino–Roesler) models, which are commonly used in simulating fracture failure of metallic materials, are evaluated in this paper. The cohesive parameters of these CZMs are determined by an inverse analysis based on the modified Levenberg–Marquardt method. A finite element (FE) model is developed by employing these CZMs and used to predict fracture behaviors of steel grade 120, which is frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To examine the influence of the TSL shape on the mechanical properties of the bonded interface of IGBT modules, three commonly used TSLs [ 41 ], namely, the bilinear law, the exponential law, and the polynomial law, are selected in this paper, as illustrated in Figure 3 . The bilinear law is available in ABAQUS 2021.…”
Section: Cohesive Zone Modelingmentioning
confidence: 99%
“…To examine the influence of the TSL shape on the mechanical properties of the bonded interface of IGBT modules, three commonly used TSLs [ 41 ], namely, the bilinear law, the exponential law, and the polynomial law, are selected in this paper, as illustrated in Figure 3 . The bilinear law is available in ABAQUS 2021.…”
Section: Cohesive Zone Modelingmentioning
confidence: 99%
“…They found that the fracture toughness of the specimen decreased with the increase of the hole size. Zhao et al [17] simulated the tensile fracture process of steel plates using five different models. The five models are bilinear, polynomial, trapezoidal, exponential, and Park-Paulino-Roesler models.…”
Section: Introductionmentioning
confidence: 99%
“…A few researches on DP failure were reported, for example, fatigue failures of DPs caused by vibration [2], erosion wear generated by drilling fluid containing debris [3], static fracture characteristics studied by a cohesive zone model [4]. The effects of impact loading on dynamics responses of DPs with cracks and their fracture failure were rarely studied.…”
Section: Introductionmentioning
confidence: 99%